A comparative study of hearing outcome in patients undergoing type 1 tympanoplasty using temporalis fascia versus sliced tragal cartilage - Shinde, Vinod; Sonar, Tejal; Shah, Shikha; Kumar, Ashutosh; Satav, Anuja (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: A tympanoplasty is a surgical procedure to close a tympanic membrane perforation and reconstruct the tympanic membrane and hearing, commonly after chronic otitis media and trauma. Methods: 50 patients were divided into 2 groups and underwent type-1 tympanoplasty using temporalis fascia versus sliced tragal cartilage. The patient was placed in supine position. Antiseptic painting and draping was done. All cases were operated under local anaesthesia. Post aural approach with post aural Wilde’s incision with 15 number blade, the incision was made 5-10 mm posterior to post aural groove. Temporalis fascia graft was harvested. Tragal cartilage, incision was taken over the under surface of the tragus and tragal cartilage was sliced. Results: The mean duration of symptoms was 12.72 and 15.84 months in group A and B respectively. Reduced hearing was noted in 21 and 24 patients, ear discharge in 21 each and giddiness in 2 and 4 patients respectively in group A and B. The difference was non-significant when the symptoms were evaluated. Improvement in AB gap was significantly better in group B with a p value of 0.042. The mean improvement was 14.2 dB and 17 dB respectively. Conclusions: Type-1 tympanoplasty using the sliced tragal cartilage may be associated with better improvement in AB gap and can be regularly employed compared to temporalis fascia method.